1979
DOI: 10.1128/jb.139.1.93-97.1979
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of the phosphoenolpyruvate:glucose phosphotransferase system in fermentative bacteria

Abstract: A number of selected fermentative bacteria were surveyed for the presence of the phosphoenolpyruvate:glucose phosphotransferase system, with particular attention to those organisms which ferment glucose by pathways other than the Embden-Meyerhof-Parnas pathway. The phosphoenolpyruvate:glucose phosphotransferase system was found in all homofermentative lactic acid bacteria tested that ferment glucose via the Embden-Meyerhof-Parnas pathway, but in none of a group of heterofermentative species of Lactobacillius o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0

Year Published

1987
1987
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(45 citation statements)
references
References 30 publications
2
43
0
Order By: Relevance
“…However, it is only in the past decade that the mechanisms for transport of different sugars have been identified, and at least partially characterized in these industrially important microorganisms ( Fig. 1 and [4][5][6]). In active transport, the sugars are accumulated intracellularly in the free form and are subsequently phosphorylated by ATP-dependent kinases.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is only in the past decade that the mechanisms for transport of different sugars have been identified, and at least partially characterized in these industrially important microorganisms ( Fig. 1 and [4][5][6]). In active transport, the sugars are accumulated intracellularly in the free form and are subsequently phosphorylated by ATP-dependent kinases.…”
Section: Introductionmentioning
confidence: 99%
“…Second, since the sugar is transported and concomitantly phosphorylated, it can directly enter catabolic and anabolic pathways, hence saving ATP and favoring growth under limited energy supply conditions. The PTS was considered to be only present in homofermentative LAB (fermenting glucose through the EMP pathway) but not in heterofermentative species using the PKP pathway [3]. Recently, Saier et al [15] reported that, while growing on fructose, the synthesis of a fructose-speci¢c PTS and glycolytic enzymes is induced in Lactobacillus brevis, which allows for fructose to be metabolized via the EMP.…”
Section: Resultsmentioning
confidence: 99%
“…PEP is the phosphate donor in the phosphoryl transfer chain leading to sugar-spe-ci¢c PTS transport and phosphorylation. Hence, according to the catabolic pathway used, a di¡erent pool of PEP will be generated that would condition the transport system [1,3].…”
Section: Introductionmentioning
confidence: 99%
“…This pathway, first discovered in muscle tissue, occurs in many bacteria. The occurrence of a PTS mode of transport seems to be limited to bacteria with an EMP mode of fermentation (Romano et al, 1979), and therefore it can be expected that the enzymes of the EMP pathway are present in D. vulgaris Hildenborough, as shown in Table 2. Furthermore, the conversion of mannose-6phosphate (the product of mannose PTS transport) to fructose-6-phosphate should occur in D. vulgaris Hildenborough, as shown by the presence of mannose-6-phosphate isomerase among the proteins revealed by genome analysis (DVU0697).…”
Section: Implications Of Pts Genes In D Vulgaris Hildenborough Genomementioning
confidence: 99%